FAKTOR RISIKO TERJADINYA KETUBAN PECAH DINI PADA IBU DI RSUD MARGONO SOEKARDJO - Maya Safitri (Universitas Harapan Bangsa Purwokerto, 2009)
KPD is defined as rupture prematurely melahirkan.Faktor the factors that affect KPDinclude infection, incompetent cervix, multiple gestation, fetal abnormalities layout,malposition, pelvic Cefalo disporposi, multigravida, abnormal membranes (amnionitis andkorioamionitis), amniotomi too early, their hypermotility womb that happened a long timebefore the amniotic pecah.Penyakit diseases such as pyelonephritis, cystitis, cervicitis andvaginitis.DiRSUD Prof. Dr. Margono Soekarjo Purwokerto obtained KPD incidence in thelast 2 years has increased in 2012 in which as many as 177 cases of KPD (2.58%) and in2013 increased to 236 cases KPD (4.22%). This researsch to know the description of risk factors for premature rupture of the womengiving birth in hospitals Prof. Dr. Margono Soekarjo Purwokerto in 2008. This research is quantitative descriptive, with a retrospective approach. The sample used wasquota sampling, samples of this study was the incidence of KPD in hospitals Prof. Dr.Margono Soekarjo in 2008 were 100 maternal. Data were analyzed using univariateanalysis. The result showed most respondents did not have a twin pregnancy is 60 respondents (60%),parity respondent is risky (primiparous and grandemultipara) of 57responden (57%), age ofthe respondents is at risk (<20 the year and> 35 years) as many as 61 respondents ( 61%). Keywords: Risk Factors KPD, KehamilanKembar, Age, Parity.